2016
DOI: 10.15640/jmm.v3n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Employability Attributes required for Entry-Level Marketing Jobs in Selected Sectors in South Africa

Abstract: This study focused on the ambivalent emotions (positive and negative) experienced by obstetric services users. Identifying such emotions can help setting priorities and improving services quality, increasing patient satisfaction. It was implemented a qualitative and exploratory research, by means of personal interviews with semi-structured approach. The data was analyzed and interpreted using content analysis, direct observation and its triangulation. As main results, we highlight the understanding of ambivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…The results of the present study resemble the findings of other studies that illustrate how competences such as communication skills, initiative, business ethics, foreign language ability, overall learning ability, adaptive ability, and self-control are equally important for the international business graduates [58] as seen by company executives [26]. Similarly, other authors [38,59,60] found that skills such as personal flexibility, ambition, trustworthiness, reliability, motivation, communication skills, ability to work under pressure, communication with customers/clients, interpersonal communication with co-workers, oral presentation skills, and a willingness to learn are important for economics, management, and marketing graduates and also for social and humanities graduates [30,61,62] as seen by both graduates and companies.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the present study resemble the findings of other studies that illustrate how competences such as communication skills, initiative, business ethics, foreign language ability, overall learning ability, adaptive ability, and self-control are equally important for the international business graduates [58] as seen by company executives [26]. Similarly, other authors [38,59,60] found that skills such as personal flexibility, ambition, trustworthiness, reliability, motivation, communication skills, ability to work under pressure, communication with customers/clients, interpersonal communication with co-workers, oral presentation skills, and a willingness to learn are important for economics, management, and marketing graduates and also for social and humanities graduates [30,61,62] as seen by both graduates and companies.…”
Section: Discussionsupporting
confidence: 88%